Cognitive Behavioral Therapy Enhances Survival in Cardiac Patients Aged Under 60: 14-YEAR OUTCOMES OF THE BEATING HEART PROBLEMS PROGRAM TRIAL. Issue 3 (14th May 2023) - Murphy, Barbara M.; Navaratnam, Hema S.; Le Grande, Michael R.; Higgins, Rosemary O.; Rogerson, Michelle C.; Elliott, Peter; Worcester, Marian U. C.; Jackson, Alun C.
Abstract : This study investigated 14-yr mortality status for participants from a randomized controlled trial of the Beating Heart Problems secondary prevention program using national mortality data. The program addresses both mental and behavioral wellbeing. Participation in the program conferred a survival benefit for patients aged <60 yr but not for participants overall. Abstract : Purpose: To optimize recovery and improve prognosis, people who have had an acute cardiac event (ACE) need support to manage their cardiac risk. In 2008, we conducted a randomized controlled trial (RCT) of Beating Heart Problems (BHP), an 8-wk group program based on cognitive behavioral therapy (CBT) and motivational interviewing (MI), designed to improve behavioral and mental health. This study investigated 14-yr mortality status for RCT participants in order to evaluate the survival impact of the BHP program. Methods: In 2021, mortality data on 275 participants from the earlier RCT were obtained from the Australian National Death Index. Survival analysis was undertaken to investigate differences in survival for participants in the treatment and control groups. Results: Over the 14-yr follow-up period, there were 52 deaths (18.9%). For those aged <60 yr, there was a significant survival benefit to program participation, with 3% deaths in the treatment group and 13% deaths in the control group ( P = .022). For those aged ≥60 yr, the death rate was identical in both groups (30%). Other significant predictors of mortality included older age, higher 2-yr risk score, lower functional capacity, lower self-rated health, and having no private health insurance. Conclusions: Participation in the BHP conferred a survival benefit for patients aged <60 yr but not for participants overall. The findings highlight the long-term benefit of behavioral and psychosocial management of cardiac risk through CBT and MI for those who are younger at the time of their first ACE.